2014
DOI: 10.1007/s10620-014-3136-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a-5p Loss Up-Regulated DDR1 Aggravated Colorectal Cancer by Activating Epithelial-to-Mesenchymal Transition Related Signaling

Abstract: Our findings indicated that up-regulation of DDR1 induced by miR-199a-5p down-regulation may contribute to the development and progression of CRC, and this effect may be associated with increased invasiveness, at least in part, via activating the EMT-related signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 32 publications
5
71
0
Order By: Relevance
“…Specifically, DDR1 and WNT2, previously validated as miR-199a-5p targets (27,42), as well as LIN7C, ARHGAP12, and PALS1 shown in our earlier study were significantly and reversely changed in the bladder SMCs following the alteration of the endogenous miRNA levels by overexpression of miR-199a-5p or antimiR199a-5p. In line with these data, another study demonstrated that overexpression of miR-199a-5p led to decreased DDR1, MMP2, N-cadherin, and vimentin expression (43). In contrast, we did not observe an inhibitory effect of miR-199a-5p on mRNA and protein levels of caveolin 1 (40) either in TEU-2 cells or in the bladder SMCs, which could be attributed to the tissue specificity of the miRNA effects.…”
Section: Journal Of Biological Chemistry 7081supporting
confidence: 87%
“…Specifically, DDR1 and WNT2, previously validated as miR-199a-5p targets (27,42), as well as LIN7C, ARHGAP12, and PALS1 shown in our earlier study were significantly and reversely changed in the bladder SMCs following the alteration of the endogenous miRNA levels by overexpression of miR-199a-5p or antimiR199a-5p. In line with these data, another study demonstrated that overexpression of miR-199a-5p led to decreased DDR1, MMP2, N-cadherin, and vimentin expression (43). In contrast, we did not observe an inhibitory effect of miR-199a-5p on mRNA and protein levels of caveolin 1 (40) either in TEU-2 cells or in the bladder SMCs, which could be attributed to the tissue specificity of the miRNA effects.…”
Section: Journal Of Biological Chemistry 7081supporting
confidence: 87%
“…Accumulating evidence have established an important relationship between EMT and the acquisition of molecular and functional characteristics of cancer stem cells [23, 24]. The reduction of migration and invasion ability may be partly due to the altered EMT-related signaling, such as CDH2 by regulating transcriptional factor SNAI1 [25]. Similar observation was found in breast cancer cells, we discovered that miR-199a-5p greatly suppressed the migration and invasion ability.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, miR-199a-5p was observed to be downregulated in triple-negative breast cancer, and its levels in plasma were notably restored upon surgical resection, suggesting that it may be involved in the development of breast cancer (17). Hu et al reported that miR-199a-5p was frequently downregulated in colorectal cancer, which led to the upregulation of discoidin domain receptor 1 and the activation of epithelialto-mesenchymal transition-related signaling (16). In addition, the expression level of miR-199a-5p was significantly increased in gastric cancer tissues compared with paired normal tissues, and higher miR-199a-5p level was associated with increased lymph node metastasis and higher tumor-node-metastasis stage, suggesting that miR-199a-5p may act as an oncogene in gastric cancer (26).…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Bementioning
confidence: 99%
“…Through negatively mediation of their targets, miRs have been implicated in numerous cellular processes, including cell survival, proliferation, differentiation, apoptosis and autophagy (13). miR-199a-5p has been observed to be deregulated and important in a variety of human cancers, including gastric cancer, non-small cell lung cancer, melanoma and colorectal cancer (14)(15)(16)(17)(18). In addition, miR-199a-5p also has an inhibitory effect on autophagy (19,20).…”
Section: Introductionmentioning
confidence: 99%